Choroidal metastasis from renal cell carcinoma presenting with exudative retinal detachment - Hor, Shi Mei; Mushawiahti Mustapha, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
A 42-year-old Chinese man, known case of renal cell carcinoma with lung metastasis, was referred to Universiti Kebangsaan Malaysia Medical Centre for left eye blurring of vision for one month duration, which was worse upon waking up in the morning and cleared up after 1-2 hours. On examination, visual acuities were 6/6 in both eyes. No relative afferent pupillary defect. Left fundus showed inferonasal retinal detachment without macular involvement. No retina break, no retinitis and no choroidal lesion seen. Right eye examination was normal. Optical coherence tomography (OCT) of left eye showed subretinal fluid temporal and inferior to optic disc. Fundus fluorescein angiography (FFA) left eye showed hypofluoresence in early phase but hyperfluorescence with pin point leakage in late phase over inferonasal quadrant. Indocyanine green (ICG) showed early hypofluoresence with late pin point hyperfluoresence in the same quadrant. A clinical diagnosis of exudative retinal detachment due to choroidal metastasis secondary to renal cell carcinoma was made. The patient was planned for cyber-knife radiotherapy of his left eye but unfortunately we lost the follow up. High index of suspicion and relevant investigation are needed for patients with visual complaints and history of renal cell carcinoma to diagnose choroidal metastasis.